An Epistemological Study of Islamic Education Management Practices in the Islamic Boarding School - Zainal Efendi Hasibuan; Anhar Anhar; Syafnan Syafnan; Pahri Siregar; Nahriyah Fata (Pascasarjana Universitas KH. Abdul Chalim, 2026)
This study aims to examine the practice of Islamic education management at the Dar Al-Ma’arif Islamic Boarding School from an epistemological perspective, with a focus on integrating Islamic values with modern management theory. The main problem studied is how management in Islamic Boarding Schools functions not only as an administrative instrument but also as a manifestation of the Islamic scientific paradigm based on monotheism. The research method uses a phenomenological qualitative approach, drawing on document studies, observations, and in-depth interviews with Islamic Boarding School managers. The results of the study show that the management practice at the Dar Al-Ma’arif Islamic Boarding School is grounded in Islamic epistemology, which emphasizes the balance between rational and spiritual aspects. The contribution of this research lies in strengthening the epistemological framework for the study of Islamic education management and in offering relevant management models for the development of Islamic education in Indonesia. Islamic boarding schools have the potential to develop a management system that balances worldly and ukhrawi goals, as well as to serve as centers for moral and spiritual strengthening.